The economic feasibility of price discounts to improve diet in Australian Aboriginal remote communities. (29th June 2015) - Magnus, Anne; Moodie, Marj L.; Ferguson, Megan; Cobiac, Linda J.; Liberato, Selma C.; Brimblecombe, Julie
Abstract: Objective: To estimate the cost‐effectiveness of fiscal measures applied in remote community food stores for Aboriginal Australians. Methods: Six price discount strategies on fruit, vegetables, diet drinks and water were modelled. Baseline diet was measured as 12 months' actual food sales data in three remote Aboriginal communities. Discount‐induced changes in food purchases were based on published price elasticity data while the weight of the daily diet was assumed constant. Dietary change was converted to change in sodium and energy intake, and body mass index (BMI) over a 12‐month period. Improved lifetime health outcomes, modelled for the remote population of Aboriginal and Torres Strait Islanders, were converted to disability adjusted life years (DALYs) saved using a proportional multistate lifetable model populated with diet‐related disease risks and Aboriginal and Torres Strait Islander rates of disease. Results: While dietary change was small, five of the six price discount strategies were estimated as cost‐effective, below a 50, 000/DALY threshold. Conclusion: Stakeholders are committed to finding ways to reduce important inequalities in health status between Aboriginal and Torres Strait Islanders and non‐Indigenous Australians. Price discounts offer potential to improve Aboriginal and Torres Strait Islander health. Verification of these results by trial‐based research coupled with consideration of factors important to all stakeholders is needed.